THE PSYCHOLOGICAL RESPONS OF THE CRITICAL CARE NURSES IN CARING COVID-19 PATIENTS - Dody Setyawan; Reni Sulung Utami; Nana Rochana; Ahmat Pujianto; Failasuf Wibisono; Ardiyanto; Imam Subiyono; Sarinti; Philip Purworahyono (Jurnal Ilmu Keperawatan Medikal Bedah, 2023)
Unstable and critical conditions of Covid-19 patients require intensive care in the Intensive Care Unit (ICU) Covid-19 isolation room. The patients require intensive actions and continuous monitoring resulting in an increase in the workload of ICU nurses. ICU nurses should also wear third level Personal Protective Equipment (PPE) while dealing with Covid-19 patients. The number of patients and nurses who died has become one of the stressors for ICU nurses. ICU nurses also feel anxious and afraid of being infected, feel worried about the effectiveness of PPE, and the risk of transmission to family members at home. This condition leads to stress, depression and affects the quality of service. Therefore, this study aims to know the psychological respons of the critical care nurses in caring Covid-19 patients. This study used descriptive survey with the sample size of 181 respondents. The respondents were members of the Central Java-Indonesian Critical Care Nurses Association recruited by some inclusion and exclusion criteria. Depression, Anxiety, and Stress Scale 42 (DASS 42) was used as an instrument to collect the data. The data were analyzed in frequency and percentage. The results showed that the majority of respondents did not experience anxiety (58%), stress (82.3%), and depression (72.9%) although there were still severe and very severe anxiety levels (11.6%), a severe stress level (2.8%), and a severe depression level (1.7%) experienced by the respondents respectively. Nurses who are anxious, stressed or depressed should obtain serious attention from the nurses, the hospital and the government. Therefore, the psychological management of nurses can be improved to prevent unwanted problems such as ongoing depression or burnout syndrome.